Absence of Cytochrome P450-1b1 Increases Susceptibility of Pressure-Induced Axonopathy in the Murine Retinal Projection - Amirmokhtari, Naseem; Foresi, Brian D.; Dewan, Shiv S.; Bouhenni, Rachida A.; Smith, Matthew A. (Frontiers in Cell and Developmental Biology, 2021)
Mutations in the cytochrome P450-1B1 (Cyp1b1) gene is a common genetic predisposition associated with various human glaucoma’s, but most prominently in primary congenital glaucoma (PCG). The role of Cyp1b1 in the eye is largely unknown, but it has been shown that its absence drives the maldevelopment of anterior eye structures responsible for aqueous fluid drainage in murine models. Nevertheless, vision loss in glaucoma ultimately results from the structural and functional loss of retinal ganglions cells. Cyp1b1’s influence in the development and support of retinal ganglion cell structure and function under normal conditions or during stress, such as from elevated ocular pressure the critical stressor most common in glaucoma, remains grossly unknown. To begin to address this, we compared the retinal projection of Cyp1b1-/- mice and age-matched wildtype controls following a 5-week period of elevated pressure induced by microbead occlusion. Prior to induction of pressure elevation Cyp1b1-/- mice demonstrate a structurally sound, normally developed retinal projection, however, reveal lower driven outer retinal activity. Following pressure elevation, Cyp1b1-/- accelerated degradation of anterograde axonal transport from the retina to the superior colliculus and altered the morphology of the node of Ranvier and adjacent paranode in the optic nerve. Based on this data, we propose that the absence Cyp1b1 expression alone is insufficient to drive murine glaucomatous pathology, however, may increase the vulnerability of retinal neurons to disease relevant elevations in ocular pressure.